Model of marine fish landing in Terengganu using Cubic B-Spline, discrete least square and exponential smoothing / Alvanie Dilyazie Ajis & Noor Fithriyah Burhanuddin - Ajis, Alvanie Dilyazie (2019)
This paper explains the best method to predict the number of fish landings using comparison between cubic B-splines, cubic least square method and exponential smoothing. Data of fish landings from the year 2015 to 2017 is obtained from the official website of Malaysia Fishery Department. By using all three methods, the data from 2015 until 2017 is calculated and the result is compared to the actual data. The error of all methods is determined using relative error. The method with the least error is chosen as the best method.